The Impact of eWOM on The Intention to Choose Green Tourist Destinations for Vietnamese Tourists - Trinh Le Tan (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to evaluate how EWOM influences Vietnamese visitors' inclinations to travel to environmentally friendly areas. (Which investigates the theories of source EWOM (EW), Environmental Concern (EC), Travel Motivation (TM), Destination Image (DI), Attitude (ATD), and Subjective Norm (SN) and constructs highly accurate structural models (SEM).Design/methodology/approach – An online survey investigated the influence of EWOM and related parameters on the intention of Vietnamese tourists to pick a green tourist location. Using Google Forms, the minimal sample size for this study will be 197 (n=197). CFA and SEM will be run on the data for testing hypotheses. Reliability statistics of the scale will be conducted by using Cronbach's Alpha, EFA.Findings – The findings of this study will help tourism organizations and marketers in Vietnam recognize that the use of eWOM by travelers in selecting a green travel destination is becoming a significant trend